2021
DOI: 10.1107/s2052520620016650
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, crystal structure and structure–property relations of strontium orthocarbonate, Sr2CO4

Abstract: Carbonates containing CO4 groups as building blocks have recently been discovered. A new orthocarbonate, Sr2CO4 is synthesized at 92 GPa and at a temperature of 2500 K. Its crystal structure was determined by in situ synchrotron single-crystal X-ray diffraction, selecting a grain from a polycrystalline sample. Strontium orthocarbonate crystallizes in the orthorhombic crystal system (space group Pnma) with CO4, SrO9 and SrO11 polyhedra as the main building blocks. It is isostructural to Ca2CO4. DFT calculations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 28 publications
(29 reference statements)
8
30
0
Order By: Relevance
“…Calculations in which a low spin state was imposed gave too small lattice parameters, which differed markedly from the experimental values. Similar to recent results on other carbonates in which the carbon is fourfold coordinated by oxygen [24,25], the DFT calculations show that all C-O bonds are covalent, with bond populations ranging from 0.8-0.6 e − /Å 3 . The carbon atoms are therefore tetrahedrally coordinated by oxygen and thus sp 3 hybridized.…”
Section: Computational Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Calculations in which a low spin state was imposed gave too small lattice parameters, which differed markedly from the experimental values. Similar to recent results on other carbonates in which the carbon is fourfold coordinated by oxygen [24,25], the DFT calculations show that all C-O bonds are covalent, with bond populations ranging from 0.8-0.6 e − /Å 3 . The carbon atoms are therefore tetrahedrally coordinated by oxygen and thus sp 3 hybridized.…”
Section: Computational Resultssupporting
confidence: 85%
“…These investigations allowed us to derive an understanding of pressure-induced structural phase transitions and changes in the structure-property relations and the electronic state, depending on thermodynamic conditions and composition [7][8][9][10][11][12][13][14][15]. Only recently has it been shown that carbonates in which carbon is tetrahedrally coordinated by oxygen atoms, i.e., sp 3 -hybridized carbon, are stable at high pressures [16][17][18][19][20][21][22][23][24][25]. Specifically, at conditions prevalent in the deeper mantle with pressures >50 GPa, siderite (FeCO 3 ) transforms via self-oxidation-reduction reactions into new phases containing sp 3 carbon [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The angles between C–O bonds correspond to that of an ideal tetrahedron with deviations of 4.5–5° for Sr 2 CO 4 - Pnma and Ba 2 CO 4 - Pnma , 0.2° for Sr 3 CO 5 - I 4/ mcm , and 1–3° for Ba 3 CO 5 - I 4/ mcm at 50 GPa. The Mulliken population analysis performed by Laniel and co-authors has confirmed the covalent nature of all four C–O bonds within the [CO 4 ] tetrahedron of Sr 2 CO 4 - Pnma .…”
Section: Resultsmentioning
confidence: 83%
“…Our results on the stability of the orthocarbonates of the other alkaline-earth metals, in particular Sr 2 CO 4 - Pnma , have been presented in the form of a conference presentation and the corresponding book of abstracts . A recent experimental synthesis has confirmed the existence of the Sr 2 CO 4 - Pnma phase …”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation